Code Mix Analysis (Arabic-Korean) of Bilingual Events on Rafiq TV's YouTube Channel - Syaphalarisa Sulthoni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is to find out what forms of code mixing are. The type of research taken is qualitative, detective research which aims to analyze and describe the language and language varieties that give rise to the use of code mixes, code mix forms. The method used to collect data is to listen carefully. Researchers only listen to and record the dialogue that is taking place. Research uses recording techniques because the data taken is data on spoken language use, so recording equipment is needed to capture how language is mixed on the Rafiq TV YouTube channel. The research results show that the code mix forms found in this research are code mixes in the form of words, phrases and clauses. As for code mixes in the form of words totaling 10 data, phrases totaling 3 data and clauses totaling 5 words 2.